Chitosan-based hydrotalcite nanostructured membranes containing sodium alendronate for guided bone regeneration therapy - Fábio Luiz Costa de Souza, Alice Simon, Evandro Lúcio Barcelos D’Ornellas, Raphael Ferreira da Silva, Ana Carolina Mattos Covas, Carlos Rangel Rodrigues, Luiz Claudio Rodrigues Pereira da Silva, Flávia Almada do Carmo, Lucio Mendes Cabral (Journal of Applied Pharmaceutical Science, 2023)
Guided bone regeneration is commonly applied in clinical dental practice for alveolar bone reconstruction. This work aims to develop nanostructured membranes with chitosan, hydrotalcite, and sodium alendronate for guided bone regeneration. Low, medium, and high molecular weight chitosan membranes were prepared to contain hydrotalcite or nanoparticulate hydrotalcite and sodium alendronate added directly in the polymer matrix or interlayered between clay lamellae. The membranes were analyzed for nanocomposite formation by X-ray diffraction and differential scanning calorimetry analyses, and water absorption and tensile strength were also assessed. In vitro assays using Saos-2 cells checked the biocompatibility, cell viability, and osteoinduction potential of the membranes. The chitosan and hydrotalcite physical mixture membrane series did not form nanocomposites and collapsed in the water absorption test. Membranes with nanoparticulate hydrotalcite with sodium alendronate interspersed formed nanocomposites and showed a good profile of water absorption and tensile strength. All nanocomposite membranes were biocompatible and demonstrated potential for osteoinduction in vitro. The membranes of the nanoparticulate hydrotalcite series presented the best performance in the in vitro assays, especially the membrane formed with low and medium molecular weight chitosan, representing a potential new therapy for guided bone regeneration, which should be tested in vivo in the near future.
Keywords: Chitosan, guided bone regeneration, hydrotalcite, membrane, nanocomposite, sodium alendronate